If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(b + 8) = 17 + 7b Reorder the terms: 4(8 + b) = 17 + 7b (8 * 4 + b * 4) = 17 + 7b (32 + 4b) = 17 + 7b Solving 32 + 4b = 17 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 32 + 4b + -7b = 17 + 7b + -7b Combine like terms: 4b + -7b = -3b 32 + -3b = 17 + 7b + -7b Combine like terms: 7b + -7b = 0 32 + -3b = 17 + 0 32 + -3b = 17 Add '-32' to each side of the equation. 32 + -32 + -3b = 17 + -32 Combine like terms: 32 + -32 = 0 0 + -3b = 17 + -32 -3b = 17 + -32 Combine like terms: 17 + -32 = -15 -3b = -15 Divide each side by '-3'. b = 5 Simplifying b = 5
| -7p-39=-3(5p-3) | | 10(x+3)-(-9x-4)=n-5+3 | | -4(-k-2)=2k-34 | | 9+3-7-8+18-3= | | 6(-1-6x)=-6-6x | | X+2x^2=36 | | 1/6+x/9=x/12 | | 38+8n=-6(1+6n) | | 2x-2y+3x= | | 0.8x=128 | | y^2+361/4=-19y | | 12d^2-d-6=0 | | 3bx*x-2ax+3b=0 | | 3bx*x-2ax+3y=0 | | 3bx*x-2ax+by=0 | | x^6-1/27=0 | | 4n+7n= | | -8(x-8)+x=2(7-x) | | x(x-6)=x^2+4x+3 | | x(x-6)=x^2+6x+11 | | 5x^2-11x-4=0 | | 60(5/12) | | 60(4/5) | | 60(x/4) | | 12(2k+11)=12(2k-12) | | -7-(-1)/-8-(-3)=-6/(-5) | | 2(3y-5)=44 | | 4r^2+9=125 | | 9x-2(x-6)=7(x+1)+2 | | 2(x+9)=19 | | 4x+4=60 | | 11r+5=-2r^2 |